Influence of cultivar, ripeness, blanching, drying, irradiation, and pectin recovery on alk(en)ylresorcinols in mango peels - Geerkens, Christian Hubert; Miller-Rostek, Petra; Matejka, Anna Elisabeth; Nene, Sanjay; Kammerer, Dietmar Rolf; Carle, Reinhold; Schweiggert, Ralf Martin (European Food Research and Technology, 2015)
The influence of different technological treatments on alk(en)ylresorcinol (AR) contents and pattern in mango peels was evaluated using peels from six different mango cultivars. AR concentrations were shown to highly depend on the cultivar. While high AR concentrations were observed in the analyzed monoembryonic cultivars, AR contents in the polyembryonic cultivar Nam Dokmai were significantly lower. Furthermore, for monoembryonic cultivars, AR levels in the peels of ripe fruits were found to be higher than in unripe ones, while AR levels in cv. Nam Dokmai were independent of the ripeness degree. Convective oven drying resulted in a significant reduction in AR contents when compared to lyophilization. Blanching prior to drying diminished AR yields, thus being unsuitable for satisfactory AR recovery. Gamma irradiation did not significantly affect the AR contents. Since depectinization of mango peels significantly concentrated AR amounts in the depectinized pomace, the consecutive extraction of pectin and ARs allows the dual valorization of mango peels. Considering the treatments investigated, the retention of ARs carrying saturated and unsaturated side chains did not differ under acidic conditions, heating, and irradiation, respectively. Consequently, the 1,3-dihydroxybenzene structure was concluded to be the most labile moiety of the AR molecule.
Keywords: Alkylresorcinol; By-products; Monoembryonic; Polyembryonic; Pomace; Ultrasound